2020
DOI: 10.1371/journal.pone.0238432
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting marine carbonate systems in two fjords in British Columbia, Canada: Seawater buffering capacity and the response to anthropogenic CO2 invasion

Abstract: The carbonate system in two contrasting fjords, Rivers Inlet and Bute Inlet, on the coast of British Columbia, Canada, was evaluated to characterize the mechanisms driving carbonate chemistry dynamics and assess the impact of anthropogenic carbon. Differences in the character of deep water exchange between these fjords were inferred from their degree of exposure to continental shelf water and their salinity relationships with total alkalinity and total dissolved inorganic carbon, which determined seawater buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 78 publications
2
17
0
Order By: Relevance
“…Identifying regional extremes in the marine CO 2 system is important for characterizing environmental variability, identifying where unfavorable conditions for vulnerable marine species occur more often or more intensely, and pin-pointing areas that may experience faster rates of change from anthropogenic CO 2 input (Feely et al, 2018;Hare et al, 2020). Marine CO 2 system extremes were characterized here based on pH T and arag variability and severity (Chan et al, 2017).…”
Section: Characterizing Regional Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying regional extremes in the marine CO 2 system is important for characterizing environmental variability, identifying where unfavorable conditions for vulnerable marine species occur more often or more intensely, and pin-pointing areas that may experience faster rates of change from anthropogenic CO 2 input (Feely et al, 2018;Hare et al, 2020). Marine CO 2 system extremes were characterized here based on pH T and arag variability and severity (Chan et al, 2017).…”
Section: Characterizing Regional Extremesmentioning
confidence: 99%
“…The highest estimated values were near 66 µmol kg −1 and similar to other estimates for coastal northeast Pacific surface water (Carter et al, 2019a;Feely et al, 2016); however, much lower values were evident in some locations. The Salish Sea is considered to have more moderate anthropogenic CO 2 levels (Feely et al, 2010;Hare et al, 2020;Evans et al, 2019), but the freshest areas observed in southeast AK exhibited very low anthropogenic CO 2 content. Such weakly buffered areas are likely locations that have been corrosive for aragonite prior to the industrial era.…”
Section: Estimating Past and Future Conditionsmentioning
confidence: 99%
“…Upwelling causes deep‐water renewal in all four inlets (Baker & Pond, 1995; Hodal, 2010; Lafond & Pickard, 1975; Wan et al., 2017). Upwelled water travels from the NE Pacific to Rivers Inlet along the 1,026 kgm −3 isopycnal (Hare et al., 2020) and both offshore and deep Rivers Inlet water were anomalously warm following the 2014–2016 marine heatwave (Jackson et al., 2018; Scannell et al., 2020), which accelerated the warming trend after 2016 (Figure 2a and Table 1). Rivers Inlet deep water is significantly denser than waters in Bute or Knight Inlet, yet the fact that some of the warmest deep waters in Bute and Knight Inlet were observed after 2017 suggests that, similar to Rivers Inlet, the source waters for Bute and Knight Inlet also warmed.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying regional extremes in the marine CO2 system is important for characterizing environmental variability, identifying where unfavourable conditions for vulnerable marine species occur more often or more intensely, and pin-pointing areas that may experience faster rates of change from anthropogenic CO2 input (Feely et al, 2018;Hare et al, 2020). Marine CO2 system extremes were characterized here based on pH and Ωarag variability and severity (Chan et al, 2017).…”
Section: Characterizing Regional Extremesmentioning
confidence: 99%
“…Highest estimated values were near 66 µmol kg -1 and similar to those reported for coastal surface water in other recent North Pacific studies (Carter et al, 2019a;Feely et al, 2016), however the lower values in fresher seawater have, to our knowledge, not been reported. The Salish Sea is considered to have more moderate anthropogenic CO2 levels (Feely et al, 2010;Hare et al, 2020;Evans et al, 2019), but the freshest areas observed in the Alexander Archipelago exemplify unique settings with very low anthropogenic CO2 content and where conditions have likely been corrosive for aragonite over most of the industrial era.…”
Section: Estimating Past and Future Conditionsmentioning
confidence: 99%